LANGUAGE LEARNING STRATEGY USED BY JUNIOR HIGH SCHOOL STUDENTS - Lelono, Sabar; Margana, Margana (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
This study aims to identify the language learning strategies used by junior high school students in the 2025/2026 academic year. The background of this study is the importance of understanding and identifying students' language-learning strategies, as this can help teachers design more effective teaching methods tailored to their students' characteristics. This study uses a descriptive, quantitative method with the SILL version 7.0 questionnaire, translated into Indonesian. The research participants were 22 students, comprising 11 males and 11 females. The results showed that overall, the use of language learning strategies was at a medium level with an average score of 2.76. Metacognitive strategies (M = 2.99) were the most frequently used, followed by memory strategies (M = 2.98), cognitive strategies (M = 2.75), compensation strategies (M = 2.75), affective strategies (M = 2.66), and finally social strategies (M = 2.40). This study also revealed no significant differences in the use of language-learning strategies by age or gender. In conclusion, although students demonstrated a good level of awareness in their learning process, there is a need to increase the use of social and affective strategies to support more effective learning. The implication of this study is the importance of teachers gaining a deeper understanding of the learning strategies students use so that the teaching and learning process is better suited to their needs.